2014
DOI: 10.1155/2014/491740
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Probiotics from Philippine Commercial Dairy Products on Cancer Cells and the Effect on Expression ofcfosandcjunEarly Apoptotic-Promoting Genes andInterleukin-1βandTumor Necrosis Factor-αProinflammatory Cytokine Genes

Abstract: This study determined cytotoxicity of probiotic Lactobacillus spp. from Philippine dairy products on cancer cells and normal fibroblasts and their effects on expression of early apoptotic-promoting cfos, cjun and proinflammatory cytokine IL-1 β, TNF-α genes. Cultures were from Yakult, Bear Brand Probiotic Drink, Nido3+ Powdered Milk. Filter-sterilized supernatants from cultures of Lactobacillus spp. were evaluated for cytotoxicity to colon cancer cells (HT-29 and HCT116), leukemia cells (THP-1), and normal hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 27 publications
(25 reference statements)
0
17
0
Order By: Relevance
“…Several studies have revealed a number of beneficial effects of certain lactobacilli, such as the suppression of pathogenic bacteria in the gut and inhibition of allergic, inflammatory and neoplastic changes ( 38 41 ). Furthermore, it has been shown that lactobacilli are particularly useful in promoting gastric ulcer healing in rats, when administered as an individual probiotic strain, such as Lactobacillus rhamnosus GG ( 42 ), Lactobacillus gasseri OLL2716 ( 43 , 44 ), or Lactobacillus acidophilus ( 45 , 46 ) or as a probiotic mixture, VSL#3 ( 47 ).…”
Section: Probioticsmentioning
confidence: 99%
“…Several studies have revealed a number of beneficial effects of certain lactobacilli, such as the suppression of pathogenic bacteria in the gut and inhibition of allergic, inflammatory and neoplastic changes ( 38 41 ). Furthermore, it has been shown that lactobacilli are particularly useful in promoting gastric ulcer healing in rats, when administered as an individual probiotic strain, such as Lactobacillus rhamnosus GG ( 42 ), Lactobacillus gasseri OLL2716 ( 43 , 44 ), or Lactobacillus acidophilus ( 45 , 46 ) or as a probiotic mixture, VSL#3 ( 47 ).…”
Section: Probioticsmentioning
confidence: 99%
“…Studies have shown the pro‐apoptotic effects of Lactobacillus species on different cancer cells (Choi et al ). Shyu et al demonstrated that the probiotic supernatants up‐regulated the apoptosis gene expression in HT‐29 and HCT116 cells (Shyu et al ). Riaz et al verified that probiotic Lactobacillus strains isolated from human breast milk have anticancer properties on HeLa cells by an increase in expression of the apoptotic gene (Riaz Rajoka et al ).…”
Section: Resultsmentioning
confidence: 99%
“…isolated from Yakult did not have a significant cytotoxic effect on normal human dermal fibroblasts and THP-1 leukemia cells but were significantly cytotoxic for the HT-29 and HCT116 colon cancer cell lines. [21] When these probiotics are taken in specified doses, these have health benefits beyond the intrinsic basic nutritional contents. [22] As such, several criteria for these probiotics have been established such as the potential to resist chemical processes (bile and gastric acids), to influence metabolic activities, to persist and survive in the human gut, and to modulate the immune response.…”
Section: Discussionmentioning
confidence: 99%